2016
DOI: 10.3109/13880209.2015.1129545
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative properties of commercial Pelargonium sidoides tincture, with cell-cycle G0/G1 arrest and apoptosis in Jurkat leukaemia cells

Abstract: Context Pelargonium sidoides DC (Geraniaceae) is an important medicinal plant indigenous to South Africa and Lesotho. Previous studies have shown that root extracts are rich in polyphenolic compounds with antibacterial, antiviral and immunomodulatory activities. Little is known regarding the anticancer properties of Pelargonium sidoides extracts. Objective This study evaluates the anti-proliferative effects of a Pelargonium sidoides radix mother tincture (PST). Materials and methods The PST was characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 75 publications
2
9
0
Order By: Relevance
“…PEL+LAT were able to statistically reduce S. aureus and E. coli growth, effect that was longer than that observed for penicillin/streptomycin. The administration of the single compounds still reduced bacteria growth; however, this effect was observed at 6 h rather than at 5 h. Moreover, this effect was not due to antioxidant activity of the single compounds as already reported [ 4 , 20 ]. Indeed, the sole compounds were not able to exert antioxidant activities, rather, they showed bacteriostatic activity although at later time points.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…PEL+LAT were able to statistically reduce S. aureus and E. coli growth, effect that was longer than that observed for penicillin/streptomycin. The administration of the single compounds still reduced bacteria growth; however, this effect was observed at 6 h rather than at 5 h. Moreover, this effect was not due to antioxidant activity of the single compounds as already reported [ 4 , 20 ]. Indeed, the sole compounds were not able to exert antioxidant activities, rather, they showed bacteriostatic activity although at later time points.…”
Section: Discussionsupporting
confidence: 72%
“…Inspired by the healing of his tuberculosis, Charles Henry Stevens introduced this phytomedical drug to England in 1897 [ 2 ], and since then, the use of this plant has increased more and more interest because of its beneficial properties. Pharmacological studies have demonstrated the usefulness of PEL in the treatment of several disorders due to its anti-inflammatory, antioxidant and immunomodulatory activities [ 3 ] and its antiproliferative effect [ 4 ]. In our very recent paper, we demonstrated that PEL together with other natural products can exert antimicrobial activities [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we found anti-proliferative activity for a commercial radix mother tincture of P. sidoides in vitro and through a bioactivity-guided approach; we isolated seven fractions with significant anti-proliferative activity [17,18]. Liquid chromatography with tandem mass spectrometry detection (LC-MS/MS) analysis of these fractions revealed the presence of phenolic compounds gallic acid, koaburaside, proanthocyanidin dimers as well as a trimer, dihydroxycoumarin sulfates, trihydroxycoumarin as well as three turgorins namely leaf movement factor (LMF) 2, LMF3 and the periodic leaf movement factor 1 (PLMF1).…”
Section: Introductionmentioning
confidence: 93%
“…Geranium essential oils are known to exhibit anti-cancer activity [21,22]. Previous studies have shown that the Pelargonium species have cytotoxic activity on cancer cells [2,7,23].…”
Section: Iscussionmentioning
confidence: 99%